Social cognitive processes explain bias in juror decisions. Issue 1 (20th October 2022) - Castrellon, Jaime J; Hakimi, Shabnam; Parelman, Jacob M; Yin, Lun; Law, Jonathan R; Skene, Jesse A G; Ball, David A; Malekpour, Artemis; Beskind, Donald H; Vidmar, Neil; Pearson, John M; Skene, J H Pate; et al.
Abstract: Jury decisions are among the most consequential social decisions in which bias plays a notable role. While courts take measures to reduce the influence of non-evidentiary factors, jurors may still incorporate biases into their decisions. One common bias, crime-type bias, is the extent to which the perceived strength of a prosecutor's case depends on the severity of the crime. Moral judgment, affect and social cognition have been proposed as core processes underlying this and other biases. Behavioral evidence alone has been insufficient to distinguish these explanations. To identify the mechanism underlying crime-type bias, we collected functional magnetic resonance imaging patterns of brain activation from mock jurors reading criminal scenarios. Brain patterns from crime-type bias were most similar to those associated with social cognition (mentalizing and racial bias) but not affect or moral judgment. Our results support a central role for social cognition in juror decisions and suggest that crime-type bias and cultural bias may arise from similar mechanisms.